Barlenses in the CALIFA survey: Combining photometric and stellar population analyses - E. Laurikainen; H. Salo; J. Laine; J. Janz (EDP SCIENCES S A, 2025)
Aims: It is theoretically predicted that, at low galaxy inclinations, boxy/peanut bar components have a barlens appearance of a round central component embedded in the narrow bar. We investigate barlenses in the Calar Alto Legacy Integral Field Area (CALIFA) survey galaxies, studying their morphologies, stellar populations, and metallicities. We show that, when present, barlenses account for a significant portion of light of photometric bulges, i.e., the excess light on top of the disks, which highlights the importance of bars in accumulating central galaxy mass concentrations in the cosmic timescale.Methods: We made multi-component decompositions for a sample of 46 barlens galaxies drawn from the CALIFA survey, where M-*/M-circle dot = 10(9.7)-10(11)(.4) and z = 0.005-0.03. Unsharp masks of the Sloan Digital Sky Survey (SDSS) r'-band mosaics were used to identify the boxy/peanut or X-shaped features. Barlenses are identified in the images using our simulation snapshots as an additional guide. Our decompositions with GALFIT include bulges, disks, and bars as well as barlenses as a separate component. For 26 of the decomposed galaxies the CALIFA DR2 V500 grating data cubes were used to explore stellar ages and metallicities at the regions of various structure components.Results: We find that 25 +/- 2% of the 1064 galaxies in the whole CALIFA sample show either X-shaped or barlens features. In the decomposed galaxies with barlenses, on average 13% +/- 2% of the total galaxy light belongs to this component, leaving less than 10% for possible separate bulge components. Most importantly, bars and barlenses are found to have similar cumulative stellar age and metallicity distributions. The metallicities in barlenses are on average near solar, but exhibit a large range. In some of the galaxies barlenses and X-shaped features appear simultaneously, in which case the bar origin of the barlens is unambiguous.Conclusion: This is the first time that a combined morphological and stellar population analysis is used to study barlenses. We show that their stars are accumulated in a prolonged time period concurrently with the evolution of the narrow bar.